2016
DOI: 10.1063/1.4954667
|View full text |Cite
|
Sign up to set email alerts
|

The structure and electronic properties of hexagonal Fe2Si

Abstract: On the basis of first principle calculations, we show that a hexagonal structure of Fe2Si is a ferromagnetic crystal. The result of the phonon spectra indicates that it is a stable structure. Such material exhibits a spin-polarized and half-metal-like band structure. From the calculations of generalized gradient approximation, metallic and semiconducting behaviors are observed with a direct and nearly 0 eV band gap in various spin channels. The densities of states in the vicinity of the Fermi level is mainly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…The optimized lattice constants of Fe 2 Si bulk with HSE06 method are a = b = 4.07 and c = 5.11 Å, agreeing well with experimental values . The spin-polarized electronic band structures of Fe 2 Si calculated with PBE method exhibit half-metallic-like property, as shown in Figure S1 (see Supporting Information), which is consistent with previous theoretical study at the same calculation level . Considering the strong-correlated effect, however, the electronic band structure calculated with the screened HSE06 hybrid function indicates that the hexagonal Fe 2 Si is a ferromagnetic metal, as shown in Figure c.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The optimized lattice constants of Fe 2 Si bulk with HSE06 method are a = b = 4.07 and c = 5.11 Å, agreeing well with experimental values . The spin-polarized electronic band structures of Fe 2 Si calculated with PBE method exhibit half-metallic-like property, as shown in Figure S1 (see Supporting Information), which is consistent with previous theoretical study at the same calculation level . Considering the strong-correlated effect, however, the electronic band structure calculated with the screened HSE06 hybrid function indicates that the hexagonal Fe 2 Si is a ferromagnetic metal, as shown in Figure c.…”
Section: Resultssupporting
confidence: 88%
“…Experimentally, single phase Fe 2 Si alloy can be obtained by a rapid quenching technique . With novel high-saturation magnetization, low coercivity, high permeability, low magnetostrictive coefficient, low magnetocrystalline anisotropy, and possible half-metallic like band structure, Fe 2 Si has great potential applications in high-power transformers, microwaves, motors, high-frequency applications, and so forth. , …”
Section: Methodsmentioning
confidence: 99%
“…Sun et al reported MAE values with the screened hybrid Heyd-Scuseria-Ernzerhof (HSE06) functional smaller than with PBE for 2D Fe 2 Si [65,66]. Chi Pui Tang et al calculated some electronic properties for bulk Fe 2 Si finding that the densities of states in the vicinity of the Fermi level is mainly contributed from the d-electrons of Fe [67]. In Table 3, we observe that the overall anisotropic magnetostriction given by MAELAS is rather small, which makes this material interesting for high-flux core applications because it can reduce hysteresis loss [68].…”
Section: Cell Relaxation Mae and Magnetostrictive Coefficientsmentioning
confidence: 99%
“…例如, 针对具有磁性的Fe 2 Si体相结构 [58,59] , 通过截取 特定的二维区域, 能够形成六方密堆、具有准单原子 层厚度的特殊二维结构 [57] , 如图3所示. 在该结构中, [67] ; 通过氢化石墨烯表面 可以获得石墨烷 [68] ; 通过硅烯 [69] 表面硅原子、二聚 体、一维原子链修饰, 可以获得具有半导体特性的二 维硅结构 [70] ; 从MoS 2 结构出发, 通过原子替换可以获 [57] (网络版彩图) 属, X=S、Se、Te) [71,72] ; 此外, 基于应力 [73] 与表面化学 修饰 [74] 等方法可以诱导二维过渡金属硫族化合物中 的相变, 如形成独特的三聚体或者链状结构, 如图5所 示 [75,76] .…”
Section: 此外 针对材料的其他性能 如带隙、硬度与电子unclassified